WALI NIKAH DALAM FIQH DAN PENERAPANNYA DALAM UNDANG-UNDANG KELUARGA ISLAM BRUNEI (PINDAAN 2012) - Nurol Huda binti Pehin Datu Seri Maharaja (Nurani, 2017)
Guardians are an important component in the ceremony of marriage for Muslim. The objective of article is to review the status of a guardian in determining the validity of a marriage, explaining the type of guardians and conditions that need to be present. In addition, the study also wanted to explain the requirement of the guardian's permitt in marriage under the Brunei Islamic Family Law (Pindaan 2012). The analys of this article will expose the opinions in the four models of fiqh along with their proofs rather than the source of the Qur'an, the Sunnah and so on. The next review will review the implementation of the fiqh within the Brunei Family Law. The study will also examine the aspects of equality and disagreements in the four sects and allotments in the law. The result of the study found that the guardian is the determinant of marriage validity according to the jumhur ulama and Syara 'Law derived from the Syafi'i fiqh.